Refractory vasodilatory shock secondary to metformin overdose supported with VA ECMO. (2022) - Ives Tallman, Crystal; Zhang, Yu; Black, Nicholas; Lynch, Kara; Fayed, Mohamed; Armenian, Patil
Graphical abstract: Highlights: Metformin overdose can lead to vasodilatory shock refractory to medical management. Extracorporeal circulatory support with venoarterial ECMO is an effective way to manage profound shock associated with metformin overdose. We report the highest recorded serum metformin level in the literature to date. Abstract: Metformin overdose may result in vasodilatory shock, lactic acidosis and death. Hemodialysis is an effective means of extracorporeal elimination, but may be insufficient in the shock setting. We present a case of a 39 yo male who presented with hypotension, coma, hypoglycemia, and lactate of 6.5 mmol/L after ingesting an unknown medication. Metformin overdose was suspected, and he was started on hemodialysis. He developed profound vasoplegia refractory to high doses of norepinephrine, vasopressin, epinephrine and phenylephrine. Venoarterial extracorporeal membrane oxygenation (VA ECMO) was initiated and he had full recovery. Serum analysis with high resolution liquid chromatography mass spectrometry revealed a metformin level of 678 μg/mL and trazodone level of 2.1 μg/mL. This case is one of only a handful of reported cases of metformin overdose requiring ECMO support, and we report the highest serum metformin levels in the literature to date. We recommend early aggressive hemodialysis and vasopressor support in all suspected cases of metformin toxicity as well as VA ECMO if refractory to these therapies. Objective: We present a case of vasodilatory shock secondary to metformin overdose requiring venoarterial extracorporeal membrane oxygenation (VA ECMO) support. This case is one of only a handful of reported cases of metformin overdose requiring ECMO support, and we report the highest serum metformin levels in the literature to date. Data sources: University of San Francisco, Fresno. Study design: Case report. Data extraction: Clinical records and high resolution liquid chromatography mass spectroscopy analysis. Data synthesis: None. Conclusions: Venoarterial ECMO provided an effective means of hemodynamic support for a patient with severe metformin toxicity.